Investigations in the strength of glulam multilayered beams under a short-time shear/Medinių klijuotų daugiasluoksnių sijų stiprumo tyrimai veikiant trumpalaikėms skersinėms skersinėms jėgoms - Čechavičius, Rimantas (Journal of Civil Engineering and Management, 1998)
The author of the article has performed wide-range tests of glulam beams. The objective of the tests is increasing of load bearing capacity of such beams under shear. As a result 5 inventions have been suggested and confirmed. In total 44 beams of various types were tested under the action of short and long-time loadings. These investigations have verified a new method for increasing load bearing capacity of glulam beams. The essence of the method was the utilisation of prestressed elements in multilayered beams. It allows to increase load bearing capacity of such elements under shear and decrease or eliminate the influence of lateral tension stresses on their resistance. Totally, 30 beams have been tested for the influence of short-time forces: 6 of them are multilayered with pre-stressed elements, made by the offer of invention No 954237; 8 analogous beams for comparison of the results are made of squared timber, board package, multilayered without prestressed elements; 16 different beams for additional investigations of methods of experiments and closer definition of separate technological factors. All beams failed because of shear. It has been proved by experiments that plywood brass in multilayered beams not only increases the strength of the beam, but also prevents the element from a sudden failure, increases its reliability. Longitudinal cracks have appeared in the zones of neutral axes of prestressed multilayered beams before the failure of them, while the load was 0,93–0,98 of ultimate the width of the crack was 0,7–0,8 mm, and the shear deformation was 2–6 mm at the moment of failure. The strength of the beams under short-time shear depending on the level of prestressing force (σy = 1,5…2,25 MPa) increased 9–10% and crack resistance increased 9–22% in comparison with unpresstressed beams. A short description of invention No 954237 has also been given (see Fig 6). Layers of a load bearing multilayered element with wood fibres oriented along the axis of the member (1) are precompressed laterally to the wood fibres (5). Compression force should not cause stresses (σy) higher than the point of wood proportionality in lateral direction. These layers (1) are glued with the layers where wood fibres are directed laterally to the axis of the element (2) and they are shorter in value Δ ≥ σy · h/E90 than layers (1). Horizontal prestressing of multilayered element (4) has to ensure a qualitative cohesion. It is possible to use structural plywood instead of wood layers with fibres lateral to the axis of the element. The use of this method does not only increase the resistance of glulam elements to short-time shear, but also ensures a better reliability of such structures.First Published Online: 26 Jul 2012